STRATEGI PENINGKATAN PENDAPATAN PETANI GAMBIR DI NAGARI SUNGAI ANTUAN KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - Reka Maulidina Maulidina (JURNAL BUANA, 2022)
ABSTRACT This study aims to (1) describe the income of gambir farmers in Nagari Sungai Antuan, Mungka District, Lima Puluh Kota Regency. (2) Describe strategies that can be used by gambir farmers to increase income in Nagari Sungai Antuan, Mungka District, Lima Puluh Kota Regency. This type of research is quantitative research using SWOT analysis. The data collection technique in this research is by interview observation and documentation. The informants involved in this study were gambir farmers in Nagari Sungai Antuan, Mungka District, Lima Puluh Kota Regency, as many as 28 gambier farmers. The results of this study can be seen that (1) The income of gambier farmers in the study area shows that the average income per gambier farmer is Rp. 27,082,143/month, which is the result of reducing total income with production costs. (2) Then the position of the strategy for increasing the income of gambir farmers in Nagari Sungai Antuan, Mungka District, Lima Puluh Kota Regency is in quadrant I with an Aggressive Strategy (SO) which means this position has great strengths and opportunities for farmers. to increase the income of gambier farming. Steps that can be taken to increase farmers' income are the need for government support in the form of socialization to farmers or socialization to introduce gambier production to the wider community, then by optimizing the quality of gambier products in order to increase farmers' income. the selling price of gambier itself. Keywords: Strategy, Increasing Income and Gambir Farmers